Intraoperative lymphatic mapping and sentinel node biopsy: Preliminary report on the application in Uruguay of the World Health Organization's Melanoma program protocol. Presentation of the first case carried out in Uruguay and review of the bibliography - El Ters, Escandor; Rodríguez, Jorge; Priario, Julio César (Cirugía del Uruguay, 1998)
The first case in Uruguay of intraoperative lymphatíc mapping and sentinel lymph node biopsy is presented related to a multicenter study carried out by the World Health Organization melanoma program. In analysis of international literature the following are pointed out: technique, node identification, histological relation to the rest of the node region and benefits of the technique with decrease of morbility and costs.